Pengaruh Konfigurasi Terumbu Buatan Bentuk Heksagonal pada Kemampuan Peredaman Gelombang - Wirayuhanto, Harish; Armono, Haryo Dwito (Universitas Trunojoyo Madura, 2021)
An artificial reef is a structure that is placed underwater and functions as a natural coral reef. Apart from being an artificial reef, the function of artificial reefs is also as a submerged breakwater. As a breakwater, it is necessary to know the level of effectiveness in reducing waves and the impact of scouring arising from the laying of artificial reef structures. This research was conducted to determine the correlation between the ability of wave attenuation to the depth of scouring due to variations in laying (structure gap distance) and variations in waves on artificial reefs in hexagonal shape with a scale model of 1:10. From the results of research conducted at the Marine Energy Laboratory of the Department of Marine Engineering, FTK ITS obtained, for laying structures with a gap of 1D, they have better wave attenuation capabilities with a small maximum scouring depth, namely with a Kt value of 0.844 and a scouring depth of 3 cm. For the laying of the structure with a distance of 0D, it has a greater value of transmission coefficient (Kt), which is 0.911 with a greater value of the maximum scouring depth, which is 3.5 cm.